Karakteristik Biologi dan Kelimpahan Rajungan (Portunus pelagicus) di Sekitar Perairan Sumenep - Maura Syafa Hafidah; Eka Nurahemma Ning Asih; Ika Masruroh; Moch. Yusuf Kurniawan (Journal of Marine and Aquatic Sciences, 2023)
The high demand for the crab export market has resulted in the crab commodity experiencing a decline and leading to exploitation. Prediction of crab stocks in Sumenep Regency is minimal due to a need for further information regarding crab data. This study aims to determine the biological characteristics of the blue swimming crab (Portunus pelagicus), limiting blue swimming crab (Portunus pelagicus), and water quality characteristics around Sumenep. Research methods is observation methods or directly contact fishermen. Data collection included blue swimming crab biology, including morphometric aspects, which consisted of measurements of carapace width, carapace length, weight, and level of gonadal maturity. Data collection for water quality parameters used the insitu method at each research location. The results of this study were variations in the morphometric characters of the crabs in the distribution of the carapace width of the male crabs found in class 121-138 mm, as many as 137 individuals, while the female crabs were found in class 121-138 mm as many as 136 individuals, the distribution of size class based on the length of the female crab in class 60 .42-68.42mm as many as 112 people. The size class distribution of male crabs was mainly found in the 51.42-59.42mm class of 96 individuals; the distribution of size classes based on the weight in male crabs in the 126-157 gram class was 65 individuals. The size class of female swimming crabs was found in the 158-189 gram class; as many as 67 individuals applied for crabs around Sumenep. Based on the crab data collection at the first location, Talango was 289 ind/700 cm2, the second location was Tanjung Saronggi, 65 and/700 cm2, and in the third location, Gili Genting, there was as much as 104 ind/700 cm2. The waters of Tanjung Saronggi are a location that has more male crabs than female crabs. The air quality characteristics around Sumenep waters are categorized as optimal for blue swimming crab habitat.